Drilling characteristics and properties analysis of fiber reinforced polymer composites: A comprehensive review. Issue 3 (March 2023) - Jagadeesh, Praveenkumara; Mavinkere Rangappa, Sanjay; Suyambulingam, Indran; Siengchin, Suchart; Puttegowda, Madhu; Binoj, Joseph Selvi; Gorbatyuk, Sergey; Khan, Anish; Doddamani, Mrityunjay; Fiore, Vincenzo; Cuadrado, Marta María Moure
Abstract: Fiber-reinforced polymer (FRP) composites play a vital role in the production of structural and semi-structural components for engineering applications. The drilling process is a commonly employed machining process for FRP composites to join the FRP structural elements. Usually, the FRP composites possess a heterogeneous nature because of their multi-layered structure, hybridization, and the presence of multi-phase materials. Hence, common problems like delaminations, fuzzing, buckling, cracking, matrix and fiber burning occur during the drilling operations. These problems cause dimensional inaccuracy, poor surface finish, and tool wear and reduce the mechanical strength of the composites. The optimum drilling parameters (drill geometry, speed, feed, and depth of cut) selection for the specific materials is good to achieve effective drilling performance and better surface quality of the holes. Yet, little study has been done on how all of these factors affect the size of the drilled hole. The majority of drilling studies on FRPCs in the past have focused on how to improve the hole quality by maximizing processing conditions, and there has been little discussion on the correlation between drilling conditions, physical properties, and production techniques. This is what motivated to review the characteristics and properties analysis of FRP composites. As a consequence of this research, it is anticipated that scientists and researchers would place a greater emphasis on the drilling characteristic of the workpieces made from FRPCs than on other attributes. This review clearly presents an overview of FRP composites drilling that had progressed from 2000 to 2021. The analysis of different drilling conditions and parameters like thrust force, drill geometry, temperature, speed, and feed also includes the post-drilling analysis through delaminations, thermal damage, and surface roughness. Furthermore, the recent developments in carbon, glass, and natural fiber reinforced polymer composites are studied with both conventional and nonconventional drilling techniques. Based on the above studies, some future challenges and conclusions are drawn from this review.